Pathomorphology of the femoral head lesion and some clinical and morphological dependences in patients with dysplastic coxarthrosis - Hryhorovskyi, Valeriy; Babko, Andrey; Guzhevsky, Igor; Poluliakh, Dmytro; Duda, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Quantitative morphological changes in the tissues of the proximal epimetaphysis of the femur with dysplastic coxarthrosis may differ from those observed in the hip joint in other diseases. Objective: based on the study of the pathohistological characteristics of the femoral head tissue and some frequency differences between them, establish correlation dependencies between clinical and morphological parameters in dysplastic coxarthrosis patients. Methods: we studied femoral head tissue in 22 patients. Clinical parameters were taken into account — the age of patients, the duration of the disease, the intensity of the pain syndrome according to the visual analogue scale. Based on the detected pathohistological changes in the tissues of the femoral head, several morphological gradation indices were taken into account, which diversify the degree of severity of dystrophic-destructive changes. Results: in the complex of pathomorphological changes in femoral head, the most significant are: deformation of the articular surface, degeneration and destruction of articular cartilage, bone-cartilaginous growths, pathology of subchondral spongiosis tissue. They occur with different frequencies and in some cases are combined at different degrees of severity. Between the individual clinical manifestations and morphological indices of the condition of the femoral head tissues, correlation dependencies are established, which should be taken into account when predicting the degree of hip joint lesion in dysplastic coxarthrosis. Conclusions: the revealed morphological features and clinical and morphological dependencies are important for planning the fixation of the femoral component of the endoprosthesis in the case of hip replacement in patients with dysplastic coxarthrosis of different time of presentation, the type of displacement of femoral head by Crowe and the degree of disruption of joint function.